Evaluasi Atas Sistem Penggajian Dalam Kaitannya Dengan Pengendalian Intern Pada PT Dae Kwang - Hastoni, Hastoni; Suryadinata, Erick Desma (Jurnal Ilmiah Ranggagading (JIR), 2011)
Payroll system is a series of procedures relating to the management of employee data from the recording, until the payment of salary calculation. In managing these data need to be controlled from the possibility of error would tar calculation, classification, and distribution of payroll costs so that adequate control is necessary for the purpose of internal control over salary is reached. The purpose of this study was to evaluate the payroll system in leather processing companies which register, calculation and payment of salaries. The evaluation conducted to determine whether the payroll system has been implemented at the company and is expected to run in accordance with the procedures set out the management in controlling costs of salaries, and associated with internal pengendalan component of salary. This research was conducted by the author in PT. Dae Kwang, located in the Village Leuwinutug, Citeureup Subdistrict, Bogor Regency. PT. Dae Kwang is the leather processing industry company, which processed raw skins (wet blue) into semi-finished leather. In preparing this paper, the method used by writer is method deskiptif, and data collection done by: library research to obtain secondary data, and field research to obtain primary data from the company. The result showed that the PT. Dae Kwang, payroll system has been implemented fairly well. It is shown by the existence of procedures, documents and records in the payroll system which can be used to help companies find employees who commit fraud and anticipate the risks that may occur. The reports generated by the payroll system, particularly regarding the calculation of attendance and salary costs, which are used by companies as a basis for calculating salary payments, besides that the payroll system accuracy in record keeping, calculation and payment of salaries used as the basis of internal control over salary The evaluation results in this study show that there are some things of concern, among others: 1) the absence of a written job description, so that each employee work hard to define, especially when those employees do not enter or leave the company. In addition it will also cause a lack of clarity of the responsibilities of each, so it can overlap the work, 2) human resources are placed on the record in this case the finance and accounting into one section, 3) the absence of internal audit within the company to supervise and examine the course of its business, so that fraud or problems that may occur can not be solved quickly. Given these shortcomings, the risk of embezzlement and payroll data manipulation can occur. The addition of employees in the finance and internal oversight in the organizational structure as well as honesty, loyalty and responsibility of employees to be a determinant of the success of the companys internal control over salaries.